Implementation of Democratic Values at the Jagad Student Boarding School ‘Alimussirry Surabaya - Bektisiwi, Pangesthi (http://jagadalimussirry.com/, 2019)
Islamic boarding schools are a community in which kiai, ustadz / ustadzah, santri and Islamic boarding schools administrators live in one environment by basing Islamic religious values ​​accompanied by general education instilled in pesantren. Islamic boarding schools have been known as traditional educational institutions which focus on religious education and focus all decisions on kiai who are central figures making the process of democratic education not going well because of authoritarianism. But at the Islamic Boarding School Student Boarding School im Alimussirry Surabaya does not use an authoritarian system, namely using a democratic system in its daily life. Because this boarding school is classified as a modern boarding school. Democracy will be formed when democratic values ​​have developed widely, evenly, internalized and carried out as the attitude and behavior of all components of the Islamic Boarding School Student Boarding School ‘Alimussirry Surabaya. Based on observations showing that life in Islamic Boarding School Students ‘Alimussirry Surabaya has implemented democratic values, it has been shown that there is a structured boarding house management, deliberative decision making and general elections to elect the president of the BES.